IMPROVING THE SYSTEM OF TRACK MAINTENANCE - Povzner, V. O.; Prokhorov, V. M. (Science and Transport Progress, 2003)
The modern system of track service maintenance is analysed and improvement of the organization of track repair works is offered on the basis of new parameters.